Orphan Imports and Lost Exports in India’s Trade: A Quantitative Assessment of the Significance and Implications for Illicit Financial Flows - Akhter, Javaid; Tiwari, Praveen (Archives of Business Research, 2021)
Orphan imports and lost exports refer to import and export transactions that have been reported by only one of the two trading partners.They are excluded from computations of trade mis-invoicing based on comparing partner country trade statistics. We show that India’s trade with 19 trading partners over 2000-2018 not only indicates substantial trade mis-invoicing but alsosignificant orphan and lost trade in the commodities displaying mis- invoicing. We also show that the amounts involved show an uptrend and are more pronounced in imports, with the orphan imports recorded by India being more than 15 times the orphan imports recorded by partner countries. Therefore, any conclusion on illicit flows through mis-invoicing in these commodities will be incomplete without analysing the impact of orphan and lost trade. We analyse some possible causes and discuss specific commodity-level examples to demonstrate that orphan and lost trade could not only lead to re-adjustment of computed amounts of trade mis-invoicing but, in the worst scenario, indicate serious fraud, with important implications for illicit flows. The paper’s finding that only a few commodities account for bulk of the amounts in orphan and lost trade could facilitate better analysis and mitigation measures.